Deadly Contradictions The New American Empire and Global Warring - Reyna, Stephen P. (Berghahn Books, 2016)
As US imperialism continues to dictate foreign policy, Deadly Contradictions is a compelling account of the American empire. Stephen P. Reyna argues that contemporary forms of violence exercised by American elites in the colonies, client state, and regions of interest have deferred imperial problems, but not without raising their own set of deadly contradictions. This book can be read many ways: as a polemic against geopolitics, as a classic social anthropological text, or as a seminal analysis of twenty-four US global wars during the Cold War and post-Cold War eras.